2022
DOI: 10.3389/fphar.2022.822671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ibandronate Therapy on Serum Chemerin, Vaspin, Omentin-1 and Osteoprotegerin (OPG) in Postmenopausal Osteoporotic Females

Abstract: Osteoporosis is a condition in which bone mineral density is reduced due to altered bone microstructure, which results in increased skeletal fragility and incidence of various types of fractures. Adipokines such as chemerin, vaspin, omentin-1 and osteoprotegerin are involved in bone remodeling. The current study was designed to determine the changes in circulating chemerin, vaspin, omentin-1, and osteoprotegerin levels after treatment with oral ibandronate 150 mg in postmenopausal osteoporotic females. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Yet, it has been reported that there is a positive correlation between Chemerin and Th17 cell levels in asthmatic patients (Zhou et al, 2018), which hints at the participation of Chemerin in the inflammatory response of CRS. Also, animal and human studies have shown that plasma Chemerin level is correlated with bone remodeling (Han et al, 2021; Ramos‐Junior et al, 2017; Tariq et al, 2022). Bone remodeling is also unveiled to exist in CRS, and can be affected by IL‐17 (Khalmuratova et al, 2019; Khalmuratova & Shin, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it has been reported that there is a positive correlation between Chemerin and Th17 cell levels in asthmatic patients (Zhou et al, 2018), which hints at the participation of Chemerin in the inflammatory response of CRS. Also, animal and human studies have shown that plasma Chemerin level is correlated with bone remodeling (Han et al, 2021; Ramos‐Junior et al, 2017; Tariq et al, 2022). Bone remodeling is also unveiled to exist in CRS, and can be affected by IL‐17 (Khalmuratova et al, 2019; Khalmuratova & Shin, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One study assessing the changes in plasma concentrations of chemerin, vaspin, omentin-1, and osteoprotegerin flowing treatment with ibandronate in post-menopausal patients with OP found a decrease of 24% following six months of treatment. Thus, suggesting an increase in circulating chemerin may be implicated in OP ( 58 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study, examining plasma concentrations of chemerin, vaspin, omentin-1, and osteoprotegerin following treatment with ibandronate in post-menopausal patients with OP found omentin-1 concentrations to have a positive relationship with BMD in post-menopausal individuals. Omentin-1 also predicted bone strength in the hip bone ( 58 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests an important role of OPG in bone loss. [8] The authors have no funding and conflicts of interest to disclose. Research on OPG gene polymorphisms has also been carried out extensively, but there is still controversy about the effect of T950C on osteoporosis.…”
Section: Introductionmentioning
confidence: 99%